INVESTIGATION OF OPTICAL PROPERTIES AND SOLID-STATE STRUCTURE OF THIOPHENE-CONTAINING TRIARYLAMINE DERIVATIVES - BOGOȘEL, Daniel-Florin; CRIȘAN, Andreea Petronela; POP, Alexandra; TEREC, Anamaria; GROSU, Ion (Studia Universitatis Babeș-Bolyai Chemia, 2025)
The optoelectronic properties of some thiophene-containing triarylamines derived formally from triphenyl amine by enlarging one, two, or all phenyl groups with phenyl, thiophene-phenyl, bithiophene, or terthiophene units, along with the molecular structure and the supramolecular arrangement of the molecules in the lattices, were revealed by spectroscopic and, in the case of two of the compounds, single crystal X-ray diffractometry investigations. This study confirms that solid-state interactions and conformations significantly influence the absorption and emission characteristics of these compounds, essential factors in designing efficient photovoltaic materials.